Guide to modeling and simulation of systems of systems - P. Zeigler, Bernard; Sarjoughian, Hessam S. (Simulation Foundations, Methods and Applications, 2017)
This easy-to-follow textbook provides an exercise-driven guide to the use of the Discrete Event Systems Specification (DEVS) simulation modeling formalism and the System Entity Structure (SES) simulation model ontology supported with the latest advances in software architecture and design principles, methods, and tools for building and testing virtual Systems of Systems (SoS). The book examines a wide variety of SoS problems, ranging from cloud computing systems to biological systems in agricultural food crops. This enhanced and expanded second edition also features a new chapter on DEVS support for Markov modeling and simulation. Topics and features: Provides an extensive set of exercises throughout the text to reinforce the concepts and encourage use of the tools, supported by introduction and summary sections Discusses how the SoS concept and supporting virtual build and test environments can overcome the limitations of current approaches Offers a step-by-step introduction to the DEVS concepts and modeling environment features required to build sophisticated SoS models Describes the capabilities and use of the tools CoSMoS/DEVS-Suite, Virtual Laboratory Environment, and MS4 Me Reviews a range of diverse applications, from the development of new satellite design and launch technologies, to surveillance and control in animal epidemiology Examines software/hardware co-design for SoS, and activity concepts that bridge information-level requirements and energy consumption in the implementation Demonstrates how the DEVS formalism supports Markov modeling within an advanced modeling and simulation environment (NEW) This accessible and hands-on textbook/reference provides invaluable practical guidance for graduate students interested in simulation software development and cyber-systems engineering design, as well as for practitioners in these, and related areas. Dr. Bernard P. Zeigler is Emeritus Professor of Electrical and Computer Engineering and Co-Director of the Arizona Center for Integrative Modeling and Simulation (ACIMS), at the University of Arizona, Tucson, USA. He is also Chief Scientist at RTSync, Rockville, MD, USA. Dr. Hessam S. Sarjoughian is Associate Professor of Computer Science and Co-Director of ACIMS at Arizona State University, Tempe, USA.